Educating the Digital Lawyer: Selected Challenges of AI-Powered Systems in Training Law Students - Krzysztof BODZENTA (Communications of International Proceedings, 2025)
The article discusses selected challenges related to the integration of artificial intelligence (AI) tools into legal education. The motivation for addressing this topic is the dynamic development of AI technologies, which increasingly influence the educational process, combined with the lack of systematic reflection on their consequences in this field. The text is based on a review of the available literature as well as ongoing academic and institutional debates. It first identifies areas in which AI-based systems may support teaching and learning. The discussion then focuses on three main categories of challenges: pedagogical, organizational, and ethical. The analysis covers both the evolving role of the academic teacher in the face of new technologies and the institutional consequences of implementing AI at universities, as well as issues of academic integrity and equal access. The article concludes with recommendations for the sustainable and responsible use of AI in training future lawyers.
Keywords: Artificial Intelligence; AI in Law Studies; Legal Education; Law Students